Hybrid IWOPSO optimization based marine engine rotational speed control automatic system - Ahmed Samawi Ghthwan; Abdulrasul A. Al-hayder; Ali Shaban Hassooni (Institute of Advanced Engineering and Science, 2020)
Transporting industry is having an important influence on the nations’ progress. The states that having long shoreline are taking advantage of their locations in using sea transportations which is more economical than other types of transportations. One of the most economical marine transport is the diesel fueling engines. This paper is to optimize the PID controller to control the speed of the engine overcoming the navigation environmental changes such as waves, winds and other effective external factors as well as the vessel internal changes such as the shipment load, equipment’s conditions …etc. PID is optimized through the optimum selection of its parameters (KP, KI and KD). A Simulink/MatLab model of the system is designed for this purpose. The Hybrid IWOPSO (HIWOPSO) algorithm is used for finding the optimum values of the PID parameters. The engine step response with these parameters is compared to the responses with those obtained by the IWO and PSO besides the Fuzzy Logic Control (FLC).